2022
DOI: 10.1002/smll.202201343
|View full text |Cite
|
Sign up to set email alerts
|

Modulating the Oxidation State of Titanium via Dual Anions Substitution for Efficient N2 Electroreduction

Abstract: The electrocatalytic nitrogen reduction reaction (NRR) is a promising approach for renewable ammonia synthesis but remains significantly challenging due to the low yield and poor selectivity. Herein, a facile N and S dual anions substitution strategy is developed to tune the Ti oxidation states of TiO2 nanohybrid catalyst (NS‐TiO2/C), in which anatase TiO2 nanoplates with dense Ti3+ active sites are uniformly dispersed on porous carbon derived from 2D Ti3C2Tx nanosheets. The catalyst NS‐TiO2/C exhibits a super… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 70 publications
0
15
0
Order By: Relevance
“…The prepeak at 4971 eV is attributed to the quadruple‐allowed Ti 1s–3d electronic transitions, which is a typical feature of noncentral symmetry. [ 33 ] In the Fourier transform of the extended X‐ray absorption fine structure (EXAFS), no peaks related to TiO coordination (1.49 Å) and TiTi coordination (2.51 Å) are observed in Ti 1 N 3 /CTF‐10 (Figure 2c). Instead, light element bonding such as TiN or TiC first coordination shell is detected at 1.09 Å.…”
Section: Resultsmentioning
confidence: 99%
“…The prepeak at 4971 eV is attributed to the quadruple‐allowed Ti 1s–3d electronic transitions, which is a typical feature of noncentral symmetry. [ 33 ] In the Fourier transform of the extended X‐ray absorption fine structure (EXAFS), no peaks related to TiO coordination (1.49 Å) and TiTi coordination (2.51 Å) are observed in Ti 1 N 3 /CTF‐10 (Figure 2c). Instead, light element bonding such as TiN or TiC first coordination shell is detected at 1.09 Å.…”
Section: Resultsmentioning
confidence: 99%
“…5 For the eNRR, non-metal element (C or B) doped anatase TiO 2 exhibited an efficiency several times higher than that of defect-containing TiO 2 , although the mechanism for the enhancement is not clear 11,12 N and S co-doping significantly boosts the performance. A faradaic efficiency of 25.49% at À0.25 V RHE was reached, 13 which was attributed to the high density of Ti 3+ species and the improved electronic conductivity. For transition metal doping, Zheng et al found that the doping of Zr in anatase TiO 2 promotes the formation of O v sites, which deliver an excellent performance with a high ammonia production rate and a faradaic efficiency of 17.3% at À0.45 V RHE .…”
Section: Introductionmentioning
confidence: 99%
“…[16,18] Recently, TiO 2 has also attracted more and more attention as an electrocatalyst for nitrogen reduction. [19][20][21][22][23][24][25][26][27][28][29][30] It was shown that oxygen vacancy created via in situ electrolysis is active for NRR. [19] Engineering the oxygen vacancy by doping becomes a popular strategy for designing TiO 2 -based electrocatalytic NRR catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…[19] Engineering the oxygen vacancy by doping becomes a popular strategy for designing TiO 2 -based electrocatalytic NRR catalysts. For example, Zheng et al found that Zr doping can cause strain in the TiO 2 slab which promotes the formation of bi-Ti 3 + species which exhibited a Faraday efficiency of 17.3 % for NRR at À 0.45 V. [22] Carbon, [28,29] Copper, [26,27] Pd, [23] and Vanadium [21] doped TiO 2 showed similar performance; while Fe doping [24,25] or dual anion [30] doping further enhance the Faraday efficiency to about 22-26 %. These works suggest that TiO 2 is a promising candidate for electrocatalytic NRR.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation